(untitled) (VITAL, 2025)
On April 18, the VII Meeting of research groups was held with the participation of the Medical Education, Physiology, Maternal Perinatal, Neuro UAN, Regenerative Medicine, Sexual and Reproductive Health, Surgery and Psychiatry research groups, among others.